2013
DOI: 10.5812/ijb.11203
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane (NCo310) Transient Transformation Using uidA Reporter Gene

Abstract: Background: Sugarcane is a monocotyledonous crop that is cultivated in the tropical and subtropical regions of the world. One of the most important criteria, influencing the efficiency of the sugarcane transformation is known to be related to physical and biological factors during the transformation procedure. Objectives: The objective of this research was to study the response of callus induction and embryogenic callus production and to identify the major parameters controlling DNA delivery by particle bombar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
3
5
0
Order By: Relevance
“…They showed that out of the various combinations of helium pressure and target distances used in their experiments on rice calli, maximum transient GUS activity was observed at 1,100 psi pressure and 9 cm target distance. High frequency of transient GUS expression at a helium pressure of 1,100 psi and a target distance of 9 cm was also found to be optimum in many other studies (Zhang et al, 1996;Chen et al, 1998;Jiang et al, 2000;Ramesh and Gupta, 2005;Matroodi et al, 2013).…”
Section: Discussionmentioning
confidence: 62%
“…They showed that out of the various combinations of helium pressure and target distances used in their experiments on rice calli, maximum transient GUS activity was observed at 1,100 psi pressure and 9 cm target distance. High frequency of transient GUS expression at a helium pressure of 1,100 psi and a target distance of 9 cm was also found to be optimum in many other studies (Zhang et al, 1996;Chen et al, 1998;Jiang et al, 2000;Ramesh and Gupta, 2005;Matroodi et al, 2013).…”
Section: Discussionmentioning
confidence: 62%
“…In the present research, the gold particles were used as microcarriers for their biologically inert behavior, uniformity in shape, size and non-toxic nature. Efficiency of gold particles in comparison to tungsten particles as microcarriers has also been reported (Matroodi et al, 2013). Gold particles of 0.6 μm size resulted in maximum transformation efficiency in contrast to 1μm particle size.…”
Section: Discussion Discussion Discussionmentioning
confidence: 73%
“…Though, reports on successful genetic manipulations are available; however, the success rate is low (Jackson et al, 2013). A number of biological and physiological parameter affects the biolistic transformation process (Matroodi et al, 2013). As seed production is not possible in most of the region due to the lack of suitable; therefore, the induction of embryogenic calli for transformation is demanded.…”
Section: Discussion Discussion Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we obtained the maximum transformation efficiency of sugarcane calli with 8.5 µg of recombinant pGreenII0129 plasmid. Matroodi et al (2013) reported a higher concentration of plasmid as vital for enhanced transformation efficiencies; however, they used pUBI121 plasmid instead of pGreenII0129. Kim et al (2012) reported the impact of plasmid concentration on the biolistic transformation of sugarcane calli.…”
Section: Discussionmentioning
confidence: 99%